German Job Mobility and Wages - Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 1998)
The paper investigates the relative importance of job mobility for wages in comparison with the human capital framework and the industry approach. Using German panel data, changes of workplaces within the firm as well as between the firms are carefully separated from occupational changes. Results suggest: Germans are much more flexible than is generally conjectured. The internal labor market is more important than the external labor market. The job approach is the most relevant framework. Firm tenure is no relevant determinant of earnings. Past mobility and sectoral and regional factors determine individual mobility.
Keywords: J31; J62; 330; internal labor markets; intra-firmmobility; occupational changes; wages; Arbeitsmobilität; Arbeitsmarktsegmentierung; Humankapital; Deutschland